A Race for the Regs: Unified Government, Statutory Deadlines, and Federal Agency Rulemaking. Issue 2 (18th December 2018) - MacDonald, Jason A.; McGrath, Robert J.
Abstract : Theory suggests that Congress should delegate more policymaking authority to the bureaucracy under unified government, where lawmakers are less worried about the president orchestrating "bureaucratic drift." Yet, all unified governments come to an end, making broad delegations potentially advantageous to future lawmaking coalitions ("coalitional drift"). We seek to assess how lawmakers simultaneously limit the risk of each of these pitfalls of delegation. Our answer is rooted in Congress's ability to spur agency rulemaking activity under unified government. Specifically, we expect statutes passed under unified government to require agencies to issue regulations quickly and for enacting coalitions to use oversight tools to influence agency policy choices. Such "proximate oversight" allows coalitions to cement policy decisions before a new election changes the configuration of preferences within Congress and the executive branch. We assess our argument using unique data on both congressional rulemaking deadlines (1995–2014) and the speed with which agencies issue regulations (1997–2014).